Identificação de variantes de hemoglobina em doadores de sangue - Bonini-domingos, Ana C. [UNESP]; Viana-baracioli, Lígia M. S.; Bonini-domingos, Claudia R. [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e Terapia Celular, 2004)
Hemoglobinopathies are the most common genetic diseases and affect a great number of individuals in the world, with diverse clinical complications ranging from the almost unnoticeable to lethal consequences. In Brazil the occurrence of hemoglobinopathies is very frequent and influenced by the ethnical groups that are the basis of populations in different regions. The phenotype may be influenced by environmental and genetic factors and by migration. An understanding of these genetic diseases is important for the health and quality of life of the population. In this work we assessed the presence of Hb variants in blood donors from São José do Rio Preto and region, and we observed the occurrence of variants including Hb S and Hb C but in particular the so-called S-Like variants. Good determination of the forms of variant hemoglobins is very important to give better guidance to blood donors and their families, and to improve the quality of blood transfusion.
Identification of hemoglobin variants in blood donor
Keywords: Variant hemoglobins; S-Like hemoglobins; blood donors